New Ca2+ Fluoroionophores Based on the BODIPY Fluorophore - Gee, K.R.; Rukavishnikov, A.; Rothe, A. (Combinatorial Chemistry & High Throughput Screening, 2003)
Calcium (Ca2+) fluoroionophores are useful in cell-based functional assays of G-protein coupled receptor (GPCR) activation or ion channel modulation. In this paper we describe new calcium probes that improve or overcome certain deficiencies in existing probes. These new fluoroionophores are based on acylation of amino-BAPTA [BAPTA = glycine, N,N'-(1,2-ethanediyl-bis(oxy-2,1-phenylene)) bis(N-(carboxymethyl))] with fluorescent BODIPY® propionates [BODIPY = 4,4-difluoro-5,7-dimethyl- 4-bora-3a,4a-diaza-s-indacene]. The resulting probes show high affinity to aqueous calcium solutions, and respond to calcium binding with significant fluorescence increases. The BODIPY fluorophores are uncharged and their fluorescence is pH-insensitive. The wide range of excitation / emission wavelength choices available within the BODIPY fluorophore series allows several different colors of new calcium indicators to be prepared. Cell permeable versions respond well with increasing fluorescence intensities in live cells after calcium influx.
Keywords: screening